Kejadian Reaksi Obat yang Tidak Dikehendaki yang Menyebabkan Pasien Usia Lanjut Dirawat Di Ruang Perawatan Penyakit Dalam Instalasi Rawat Inap B Rumah Sakit Dr. Cipto Mangunkusumo - Christianie, Merry; Setiati, Siti; Trisna, Yulia; Andrajati, Retnosari (UI Scholars Hub, 2008)
Objectives. To determine the prevalence of adverse drug reaction related hospital ad-missions in geriatric patients, to describe the most frequent clinical manifestations and the drugs responsible to adverse drug reaction related hospital admissions. Design. Observational cross-sectional study. Methods. Naranjo algorithm used to assess the adverse drug reaction causality. Subjects and setting. Geriatric patients admitted to geriatric inpatient installation of Cipto Mangunkusumo general hospital over one month period and assessed for cause of admissions. Results. 14,7% of 102 admissions were identified to be adverse drug reaction related hospital admissions. One adverse drug reaction was categorized as definite and 14 were probable causality. Gastrointestinal bleeding and hypoglicemia were the most common clinical manifestation found. The drugs most frequent responsible for these adverse drug reactions were nonsteroidal antiinflamatory drugs and oral antidiabetic drugs. Conclusion. Adverse drug reactions are an important cause of hospital admission in geriatric patients.